Content marketing as an effective tool for promotion of goods and services on the internet - Belova, Tatyana; Gulka, Victoria (My University, 2021)
This article is devoted to revealing the essence of the concept of content marketing. The meaning of the concept "Content Marketing" is given. It has been proven that with the help of high-quality content that will be interesting and useful for a certain target audience, it is possible to build a connection between the brand and the consumer. The criteria that effective content marketing must meet are given. Recommendations for creating quality content and goals that help to achieve the use of this promotion tool are also considered. Дана стаття присвячена розкриттю сутності поняття контент-маркетингу. Надано зміст поняття «Контент-маркетинг». Доведено, що за допомогою високоякісного контенту, який буде цікавим та корисним для певної цільової аудиторії, можна вибудувати зв’язок між брендом та споживачем. Наведено критерії, яким повинен відповідати ефективний контент-маркетинг. Також розглядаються рекомендації щодо створення якісного контенту і цілей, яких допомагає досягти застосування даного інструменту просування.
Keywords: content marketing; content uniqueness; high quality content; content marketing goals; promotion; унікальність контенту; високоякісний контент; контент-маркетинг; цілі контент-маркетингу; просування; кафедра маркетингу